"Polskie miesiące": maj [blok znaczków podziemnych] . "Polish months": May. Sheet of unofficial stamps - Victor. (Poczta Solidarność, 1986)
Brown and red print on white paper, without perforation. Sheet, with "Poczta Solidarność" imprint, part of the "Polish Months" series, consists of 3 stamps which represent events in Polish history that happened in May: The first Polish Constitution (3 May 1791), the victory at Monte Cassino (18 May 1944), and street protests against the Martial Law (1 May 1982). Price: 40 zł per stamp.